Development of Alkylthiazole-Based Novel Thermoelectric Conjugated Polymers for Facile Organic Doping - Junho Kim; Eui Hyun Suh; Kyumin Lee; Gyuri Kim; Hansu Kim; Jaeyoung Jang; In Hwan Jung (Nanomaterials, 2023)
In this study, we developed two novel conjugated polymers that can easily be doped with F4TCNQ organic dopants using a sequential doping method and then studied their organic thermoelectric (OTE) properties. In particular, to promote the intermolecular ordering of OTE polymers in the presence of the F4TCNQ dopant, alkylthiazole-based conjugated building blocks with highly planar backbone structures were synthesized and copolymerized. All polymers showed strong molecular ordering and edge-on orientation in the film state, even in the presence of the F4TCNQ organic dopant. Thus, the sequential doping process barely changed the molecular ordering of the polymer films while making efficient molecular doping. In addition, the doping efficiency was improved in the more π-extended polymer backbones with thienothiophene units due to the emptier space in the polymer lamellar structure to locate ionized F4TCNQ. Moreover, the study of organic thin-film transistors (OTFTs) revealed that higher hole mobility in OTFTs was the key to increasing the electrical conductivity of OTE devices fabricated using the sequential doping method.